The serotonin transporter gene and female personality variation in a free-living passerine - Bert Thys (Nature Portfolio, 2021)
Abstract Quantifying variation in behaviour-related genes provides insight into the evolutionary potential of repeatable among-individual variation in behaviour (i.e. personality). Yet, individuals typically also plastically adjust their behaviour in response to environmental conditions and/or age, thereby complicating the detection of genotype–phenotype associations. Here, using a population of free-living great tits (Parus major), we assessed the association between single nucleotide polymorphisms (SNPs) in the serotonin transporter gene (SERT) and two repeatable behavioural traits, i.e. female-female aggression and female hissing behaviour. For female-female aggression, a trait showing age-related plasticity, we found no evidence for associations with SERT SNPs, even when assessing potential age-dependent effects of SERT genotype on aggression. We also found no strong support for associations between SERT SNPs and hissing behaviour, yet we identified two synonymous polymorphisms (exon 13 SNP66 and exon 12 SNP144) of particular interest, each explaining about 1.3% of the total variation in hissing behaviour. Overall, our results contribute to the general understanding of the biological underpinning of complex behavioural traits and will facilitate further (meta-analytic) research on behaviour-related genes. Moreover, we emphasize that future molecular genetic studies should consider age-dependent genotype–phenotype associations for behavioural trait (co)variation, as this will vastly improve our understanding of the proximate causes and ultimate consequences of personality variation in natural populations.